Customer Versus Supplier Expectations: Bringing in Value Beyond Just the Widgets - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
In a highly competitive world where the customer expects to be king, why are so many firms unhappy with the products they purchase, sales staff who over-promise and don’t deliver, and less than optimal after-sales service? In a recent paper published in the Journal of Marketing, Singapore Management University marketing professor Kapil R. Tuli and Emory University professors Ajay K.Kohli and Sundar G. Bhardwaj shed light on what appears to be a fundamental mismatch between customer expectations and what suppliers think their customers want.